Assessment Framework of Building Facade in Optimizing Indoor Thermal Comfort of Green Building Index (GBI) Certified Office Building - Tharim, Asniza Hamimi Abdul; Samad, Muna Hanim (EDP Sciences, 2016)
During the past decade, the construction industry has seen a new trend in the development of “green” or “sustainable” construction concept around the world with vast support from prominent organization, together with the introduction of sustainable building codes. The establishment of green building certification systems worldwide is seen as one of the most efforts in the emerging green building movement. In order to support the development of the “green” and “sustainable” concept in Malaysia, Green Building Index (GBI) was launched by the government on 21 May 2009 that created to promote sustainability in the built environment and raise awareness of environmental issues. However, the construction industry seems to have focused only on findings the "right mechanism" for an environmentally sustainable "final result" in order for the building to be certified as green with the lacking of continuous assessment on the building performance after the certifications. This study is purposely conducted to investigate the performance of various rated Green Building Index (GBI) Non-Residential New Construction office buildings and the influence on Indoor Thermal Comfort (ITC) of the selected buildings. The aim is to develop an assessment framework for optimum green building architectural façade to be used for office buildings in Malaysia as well as to analyse the occupants’ perception, satisfaction and performance in the selected Green Building Index (GBI) rated office indoor environment. This research is still in its infancy; therefore the paper is focused on research aims, research scope and methodology, and expected deliverables for the proposed research.